The Rohingya Crisis and the International Criminal Court - Takemura, Hitomi (Springer, 2023)
The purpose of this book is to critically examine the activities of the International Criminal Court (ICC) on the eve of its 20th year of existence, with a focus on its relationship to the Rohingya crisis. This book is unique in that it identifies the potential and contemporary challenges of the ICC while focusing on the relationship between the Rohingya issue and the ICC. The relationship between the Rohingya crisis and the ICC is an issue that is fraught with contemporary challenges and worth dealing with. The relationship between the ICC and non-State Parties and the relationship between the ICC and high government officials are the examples of these challenges. Its novelty is to address the relationship between the Rohingya crisis and the ICC by staying current of information. The human rights situation of the Rohingya is of high international concern. With a case pending at the International Court of Justice (ICJ), not only individual criminal responsibility but also State responsibility may be sought for the most serious human rights violations. The Rohingya crisis itself is of great international concern, and it is expected that the issues will be discussed from the perspective of international human rights law, international humanitarian law, and international criminal law. Therefore, the structure of this book is as follows. First, it explains the history of the Rohingya crisis. Secondly, it touches on the relationship between the Rohingya crisis and the ICC. Thirdly, the book discusses the relationship between the ongoing case of Gambia v. Myanmar at the ICJ and the proceedings of the ICC. Finally, the book concludes with an assessment of the legitimacy, effectiveness, and efficiency of the ICC in recent years.